Andrew J. Kunka. Autobiographical Comics. New York: Bloomsbury Academic, 2017. - Nicole Dib (Studies in 20th & 21st Century Literature, 2017)
Review of Andrew J. Kunka. Autobiographical Comics. New York: Bloomsbury Academic, 2017.
Keywords: autobiographical comics; comics studies; graphic life writing